2017
DOI: 10.1016/j.eplepsyres.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous lacosamide in status epilepticus: Correlation between loading dose, serum levels, and clinical response

Abstract: High intravenous LCM loading doses (>9mg/kg) were associated with serum levels within the reference interval, there was however no correlation with the clinical response. Prospective studies are needed to evaluate the benefit of increasing the LCM loading dose in SE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
1
22
2
2
Order By: Relevance
“…Plasma levels may thus be of limited help to predict the availability of treatment at its biological target. Fourthly, the relationship between blood or brain exposure and therapeutic efficacy might display important between-patient pharmacodynamic variability: a similar observation was done for lacosamide in the same clinical setting (Perrenoud et al, 2017). Making a parallel with chronic epilepsy in an outpatient setting, most of the medication effect in responders is usually obtained at low dosage, and increasing doses seem to bring little additional benefit in terms of remission (D'Anto et al, 2017;Poolos et al, 2017) Our response rate to LEV was 34%, lower than previous studies with similar dosages that reported rates of 68.5% in 204 episodes (Yasiry and Shorvon, 2014), or 65.4% in 156 episodes (Trinka and Dobesberger, 2009).…”
Section: Discussionmentioning
confidence: 75%
“…Plasma levels may thus be of limited help to predict the availability of treatment at its biological target. Fourthly, the relationship between blood or brain exposure and therapeutic efficacy might display important between-patient pharmacodynamic variability: a similar observation was done for lacosamide in the same clinical setting (Perrenoud et al, 2017). Making a parallel with chronic epilepsy in an outpatient setting, most of the medication effect in responders is usually obtained at low dosage, and increasing doses seem to bring little additional benefit in terms of remission (D'Anto et al, 2017;Poolos et al, 2017) Our response rate to LEV was 34%, lower than previous studies with similar dosages that reported rates of 68.5% in 204 episodes (Yasiry and Shorvon, 2014), or 65.4% in 156 episodes (Trinka and Dobesberger, 2009).…”
Section: Discussionmentioning
confidence: 75%
“…Although LCM is not FDA approved for SE, it has been evaluated in this setting in multiple case series, case reports, and retrospective reviews . The populations studied varied in the types of SE encountered: generalized, convulsive, absence, focal, complex partial, nonconvulsive, refractory, and super refractory (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…However, doses of concomitant AEDs were not evaluated as confounders in this study, and serum levels were not obtained to correlate with LCM dosing. One retrospective investigation of 40 patients found no correlation between LCM serum levels and clinical response, but doses of greater than 9 mg/kg resulted in serum levels of 10–20 mg/L . Optimal target serum levels in SE have not been defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Эффективность применения лакосамида при эпилептическом статусе подтверждается в ряде клинических исследований (33,34,35). В частности, в сравнительном исследовании между вальпроевой кислотой и лакосамидом эпилептический статус удалось купировать в 66,7 % и 69,7 % случаях, соответственно.…”
Section: научные статьиunclassified